Amazon Alexa beyond the basics : learn the advanced techniques Alexa champions use to create winning Alexa skills - Peterson, Terren (O'Reilly, 2017)
"Creating advanced Amazon Alexa skills requires a more sophisticated set of tools than the elementary ones described on Amazon's web site. In this course, Terren Peterson reveals the tools and processes employed by Alexa Champions. You'll gain experience designing advanced voice user interfaces, learn about the Speech Synthesis Markup Language, and explore ways to integrate third party APIs. You'll also pick up techniques for adding music and sound, discover how to use analytics to improve the performance of your skills over time, and learn how to add visuals to Amazon's Echo Show."--Resource description page